Open hemorrhoidectomy under local anesthesia versus saddle block in western Uganda: a study protocol for a prospective equivalence randomized, double-blind controlled trial - Franck Katembo Sikakulya; Robinson Ssebuufu; Xaviour Francis Okedi; Moris Baluku; Herman Lule; Patrick Kyamanywa (Trials, 2022)
Abstract Background While open hemorrhoidectomy under local anesthesia has been shown to be more cost-effective with shorter operation times and lower complication rates, local anesthesia is still not considered as a first-line technique in low-income countries like Uganda. The objective of this trial is to compare open hemorrhoidectomy using local anesthesia versus saddle block among patients with primary uncomplicated 3rd- or 4th-degree hemorrhoids in western Uganda. Methods The protocol for a prospective equivalence randomized, double-blind controlled trial was conducted among patients with primary uncomplicated 3rd- or 4th-degree hemorrhoids. Recruitment was started in December 2021 and is expected to end in May 2022. Consenting participants who require open hemorrhoidectomy indicated at Kampala International Teaching Hospital, Uganda, will be randomized into two groups of 29 patients per arm. Discussion The primary outcome of this study is to compare the occurrences of postoperative pain following open hemorrhoidectomy using the visual analog scale in an interval of 2, 4, and 6 h and 7 days postoperatively. Furthermore, the mean operative time from the induction of anesthesia to the end of the surgical procedure as well as the cost-effectiveness of the 2 techniques will be assessed in both groups. Open hemorrhoidectomy under local anesthesia has the potential to offer benefits to patients but most importantly expediting return to baseline and functional status, shorter hospital stay by meeting the faster discharge criteria, and reduction in costs associated with reduced length of stay and complications. Trial registration Pan African Clinical Trials Registry PACTR202110667430356. Registered on 8 October 2021